From Shock to Shift–A Qualitative Analysis of Accounts in Mid-Career About Changes in the Career Path - Nalis, Irina; Kubicek, Bettina; Korunka, Christian (Frontiers in Psychology, 2021)
Career shocks are the norm, not the exception. Yet, much of research and counselling on career-development holds unrealistic assumptions of a makeable career. Little is understood about the role of shocks on the career path and how the interplay of individual reactions to shocks shapes careers. The purpose of this study is to provide understanding of responses to different attributes of career shocks and career shocks as antecedents to career and job change. A qualitative approach was chosen and data were obtained from 25 semi-structured interviews with a sample of mid-career individuals who had experienced shocks in their work lives. The analysis was twofold and aimed at unearthing of individual responses to shocks and the question of the role of shocks on changes in the career path. Firstly, the analysis of career shocks revealed a pattern of distinct agentic responses in relation to shocks of different attributes. Secondly, from the analysis of shock attributes and corresponding responses over time career changer profiles emerged which differ in regard to career change behavior and magnitude of changes in the career (e.g., major career changes into another field). A process model which depicts how post-shock careers are shaped distinctively in relation to different shock attributes and corresponding responses is presented. This study underlines the importance of understanding the unplannable in career development and shows a variety of options for individuals to develop their careers despite shocks. Limitation stems from the investigation of a sample limited to mid-career individuals. The findings provide a new conceptual lens to theorize and conduct research on career shocks and career changes and facilitate the development of coping strategies for career shocks. The originality lies in the investigation of the momentum of career shocks on career paths with detail to different attributes of career shocks and how they impact the career path.